Phytosulfokine peptides, their receptors, and functions - Li, Yi; Di, Qi; Luo, Li; Yu, Liangliang (Frontiers in Plant Science, 2024)
Phytosulfokines (PSKs) are a class of disulfated pentapeptides and are regarded as plant peptide hormones. PSK-α, -γ, -δ, and -ε are four bioactive PSKs that are reported to have roles in plant growth, development, and immunity. In this review, we summarize recent advances in PSK biosynthesis, signaling, and function. PSKs are encoded by precursor genes that are widespread in higher plants. PSKs maturation from these precursors requires a sulfation step, which is catalyzed by a tyrosylprotein sulfotransferase, as well as proteolytic cleavage by subtilisin serine proteases. PSK signaling is mediated by plasma membrane-localized receptors PSKRs that belong to the leucine-rich repeat receptor-like kinase family. Moreover, multiple biological functions can be attributed to PSKs, including promoting cell division and cell growth, regulating plant reproduction, inducing somatic embryogenesis, enhancing legume nodulation, and regulating plant resistance to biotic and abiotic stress. Finally, we propose several research directions in this field. This review provides important insights into PSKs that will facilitate biotechnological development and PSK application in agriculture.